Carbon Nanomaterials From Metal-Organic Frameworks: A New Material Horizon for CO2 Reduction - Xuan, Xiaoxu; Chen, Songying; Zhao, Shan; Yoon, Joon Yong; Boczkaj, Grzegorz; Sun, Xun (Frontiers in Chemistry, 2020)
The rise of CO2 in the atmosphere, which results in severe climate change and temperature increase, is known as the major reason for the greenhouse effect. Reducing CO2 to value-added products is an attractive solution to this severe problem, along with addressing the energy crisis, to which the catalysts being employed are of vital importance. Due to their high porosity and tunable compositions, metal-organic frameworks (MOFs) show great potential in energy conversion systems. By thermal or chemical treatment methods, the MOFs are easily turned into MOF-derived carbon nanomaterials. The much higher level of conductivity enables MOF-derived carbon nanomaterials to be employed in CO2 conversion processes. The present review, discusses the state of the art of MOF-derived carbon nanomaterials in CO2 electrochemical, photocatalytic, and thermal reduction applications. The corresponding reaction mechanisms and influence of various factors on catalyst performance are elaborated. Finally, the deficiencies and recommendations are provided for future progress.